2021
DOI: 10.1111/btp.13009
|View full text |Cite
|
Sign up to set email alerts
|

Detecting aquatic and terrestrial biodiversity in a tropical estuary using environmental DNA

Abstract: Estuaries are characterized by a tidal regime and are strongly influenced by hydrodynamics and host diverse and highly dynamic habitats, from fresh, brackish, or saltwater to terrestrial, whose biodiversity is especially difficult to monitor. Here, we investigated the potential of environmental DNA (eDNA) metabarcoding, with three primer sets targeting different regions of the mitochondrial DNA 12S ribosomal RNA gene, to detect vertebrate diversity in the estuary of the Don Diego River in Colombia.With eDNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…As a promising method for the assessment of aquatic species diversity ( Ahn et al, 2020 ; Polanco et al, 2021 ; Tsuji et al, 2019 ), eDNA metabarcoding is strongly dependent on a molecular workflow, which involves eDNA capture, extraction, and bioinformatics analyses. Comparative studies have tested the efficiency of eDNA capture using different filtration and extraction methods as well as filtration water volumes in various settings ( Cantera et al, 2019 ; Deiner et al, 2015 ; Djurhuus et al, 2017 ; Shu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising method for the assessment of aquatic species diversity ( Ahn et al, 2020 ; Polanco et al, 2021 ; Tsuji et al, 2019 ), eDNA metabarcoding is strongly dependent on a molecular workflow, which involves eDNA capture, extraction, and bioinformatics analyses. Comparative studies have tested the efficiency of eDNA capture using different filtration and extraction methods as well as filtration water volumes in various settings ( Cantera et al, 2019 ; Deiner et al, 2015 ; Djurhuus et al, 2017 ; Shu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate water-sampling procedures for aquatic ecosystems are important for eDNA studies. Previous research has demonstrated that a large volume of filtration water is needed to represent real fauna in habitats ( Cantera et al, 2019 ; Polanco et al, 2021 ; Pont et al, 2018 ; Stauffer et al, 2021 ; Valentini et al, 2016 ). The three filtration water volumes tested in this study are commonly used in eDNA metabarcoding studies, with high success rates for species detection ( Sales et al, 2021 ; Valdivia-Carrillo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, more intensive studies to identify these areas are needed. The discovery of these threatened species highlights the value of eDNA metabarcoding as a tool for assessing biodiversity and represents a promising step towards a holistic conservation in estuaries, mangrove and coastal ecosystems 20,23,41 .…”
Section: Discussionmentioning
confidence: 99%
“…water, soil) 20,21 . It overcomes the shortcomings of conventional survey methods to e ciently characterise sh assemblages in aquatic habitats as have been reported in estuarine [22][23][24] , marine 25,26 , and freshwater ecosystems 27,28 . The use of eDNA as a powerful monitoring instrument is increasingly acknowledged as it reveals greater diversity at a lower cost compared to conventional surveying methods [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…West et al ( 2021 ) illustrates the utility of DNA metabarcoding to describe assemblages of aquatic reptiles across northern Australia, where nine aquatic reptile species were detected using a mitochondrial 16S assay designed for reptiles. Polanco et al ( 2021 ) used a mitochondrial 12S assay (VERT01 (Taberlet et al, 2018 )) to describe biodiversity in tropical Columbia in estuaries and marine waters. This primer was designed for all vertebrates, and successfully detected one species of reptile (the spectacled caiman, Caiman crocodilus ) and two families of reptile (Alligatoridae and Kinosternidea), along with several amphibians, birds, mammals, and fish (Polanco et al, 2021 ).…”
Section: Distribution Of Edna Studiesmentioning
confidence: 99%